Pengaruh Sanksi Administrasi Dan Surat Paksa Terhadap Optimalisasi Pencairan Tunggakan Pajak Pada KPP Pratama Makassar Utara - Nuramal - (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2019)
This study aims to determine the effect of Administrative Sanctions and Forced Letters on Optimizing Disbursement of Tax Arrears at the Pratama Tax Office North Makassar. Data collection uses secondary data obtained from the Pratama Makassar North Tax Service Office. The population is 36 tax payers and the sample is 36. The data analysis method uses multiple linear regression techniques. The results of this study indicate that administrative sanctions show a positive and significant. This means that administrative sanctions have a positive effect on optimizing the disbursement of tax arrears. The forced letter shows positive and significant. This means that forced letters have a positive and significant effect on optimizing the disbursement of tax arrears.